Taking forward perceptions of identity: the Sea League’s campaign to protect maritime communities and the environment. - Uisdean Cheape (Angles)
The Sea League was a significant but relatively short-lived movement of popular protest (1933-1939), active in the communities of the Outer Hebrides for the purpose of drawing the attention of government to deep concerns over island social and economic circumstances. Founded in the Island of Barra, their cause was political and public recognition of the destruction of inshore fisheries and of consequent loss of livelihoods in island communities. Through its campaign, evidenced through its newsletter and surviving correspondence, the Sea League can be seen as propagating perceptions of identity in fishing communities in the Outer Hebrides based on commonality of interests and the threats to them from a wider society. This gave their cause profile although the wider aims were only partially realised in the nearly six years of campaigning which was effectively ended by the outbreak of the Second World War. Perceptions of identity engendered by the Sea league have continued to be shaped by the culture and language of the Gàidhealtachd, and these same communities in which the language survives are engaging with the contemporary climate-crisis and current debates on environmental conservation. Considerable space is given to this to highlight the relevance of the Sea League’s campaign for the part of ‘human ecology’ in the marine environment.